The Impact of Economic Policy Uncertainty on Corporate Profitability: An Empirical Research Based on Manufacturing and Non-manufacturing Industries in China - Hong Yang (SHS Web of Conferences)
This study examines the varied effects of economic policy uncertainty (EPU) on corporate profitability using panel data of Chinese A- share listed companies from 2000 to 2022, highlighting the differences between manufacturing and non-manufacturing industries. It is found that rising EPU significantly reduces corporate profitability (ROE), but the manufacturing sector exhibits stronger risk resistance. Firms in economically developed regions are more sensitive to EPU, with profitability of firms in the eastern region being most significantly impacted. However, manufacturing industries in the region can effectively mitigate the negative impact of EPU through the concentration of innovative resources and supply chain integration. Channel analysis shows that financing constraints and capital intensity are key mechanisms to explain industry heterogeneity. This study enriches the literature on policy uncertainty and corporate performance, provides a theoretical basis for policymakers to differentiate their support policies, and offers practical insights for firms to cope with policy uncertainty.